Therapeutic alliance: satisfaction and attrition of patients from a mental health clinic in Ayacucho, Peru. Issue 4 (November 2014) - Prom, Maria C.; Stovall, Jeffrey; Bedregal, Luis E.; Phillips, James; Davidson, Mario A.
Abstract : This study examines the role of the patient–provider relationship (alliance) and patient satisfaction in early patient withdrawal from mental health therapy in rural Peru. A prospective comparison of 60 patients demonstrated that early withdrawal was associated with the clinician's, but not the patient's, evaluation of the patient–provider alliance. This suggests that the satisfaction and alliance questionnaires typically used in high-income countries may not be effective in evaluating patient attitudes in this population, but may be useful for clinician evaluations of the alliance. Clinicians can use the Working Alliance Inventory to indicate the need for early intervention to prevent patient drop-out in middle- and low-income countries.